2013
DOI: 10.1039/c2an36663k
|View full text |Cite
|
Sign up to set email alerts
|

A novel platform for enhanced biosensing based on the synergy effects of electrospun polymer nanofibers and graphene oxides

Abstract: A novel biosensing platform was developed by combining the advantages of electrospun poly(vinyl alcohol) (PVA)/chitosan nanofibers and graphene oxides (GO). Glucose oxidase (GOD) was employed as a model enzyme. By co-electrospinning the solution of PVA, chitosan, GOD and GO, the PVA/chitosan/GOD/GO nanofibers were directly modified on the platinum (Pt) electrode. The UV-vis spectra and the FTIR spectra were used to characterize the GO nanosheets. The morphologies of fabricated electrospun nanofibers were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…During the last 20 years, electronically polymers like PANi, PPy, and polythiophene have received significant attention because of their easy synthetic procedures, less time consuming, remarkable electronic, magnetic, and optical properties and their wide range of potential applications in many areas [82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: Electrochemical Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 20 years, electronically polymers like PANi, PPy, and polythiophene have received significant attention because of their easy synthetic procedures, less time consuming, remarkable electronic, magnetic, and optical properties and their wide range of potential applications in many areas [82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: Electrochemical Polymerizationmentioning
confidence: 99%
“…Wisitsoraat et al [93] developed graphene-PDEOT:PSS composite based on electrophoretic method. Su et al [94] demonstrated the synthesis of PVA-chitosan-GO nanocomposites by electrospinning the solution of PVA, chitosan, GOx and GO.…”
Section: Electrochemical Polymerizationmentioning
confidence: 99%
“…Many nanomaterials, such as carbon nanotubes [5,18], gold nanoparticles [19,20], and metal oxides [21,22] have been used in biosensors. More recently a new class of carbon material, graphene, which is a twodimensional sheet of carbon atoms, has attracted increasing attention with respect to its potential applications in phtoelectronic devices, supercapacitors, sensors and nanocomposites applications [6,[23][24][25][26][27][28][29][30][31][32]. Due to their planar morphology and thus larger accessible surface area, graphene may perform better than any other carbon-based materials for an electrode sensor fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The high sensitivity and good stability of such a modified electrode contributed to the construction of a practical glucose biosensor. Su et al [27] reported the synergy mechanism of electrospun PVA/chitosan nanofibers and graphene nanosheets for efficient glucose biosensing. These results indicate graphene shows significant potential for fabricating an electrochemical sensing interface.…”
Section: Introductionmentioning
confidence: 99%
“…21 The water stability of PVA NFs may be improved through cross-linking by exposure to glutaraldehyde solutions [22][23] or vapors. 24 but this additional posttreatment step is time-consuming and requires careful optimization to preserve enzyme conformation and activity. Some works focusing on the fabrication of electrospun NFs from enzyme/PVA blends have been already published 19,[22][23][24][25][26][27] but applications to the elaboration of enzyme electrochemical biosensors are rather scarce.…”
mentioning
confidence: 99%